Effects of the essential oil of Lippia gracilis Schauer on caulinary shoots of heliconia cultivated in vitro Efeito do óleo essencial de Lippia gracilis Schauer sobre ápices caulinares de heliconia cultivadas in vitro - C.C. Albuquerque; T.R. Camara; A.E.G. Sant'ana; C. Ulisses; L. Willadino; C. Marcelino Júnior (Universidade Estadual Paulista, 2012)
The effects of thymol and carvacrol and the essential oil of Lippia gracilis on caulinary shoots of heliconia were evaluated. After disinfection, the shoots were inoculated into MS medium and subjected to the treatments with 420 µL L-1 of essential oil (EO) of L. gracilis; 420 µL L-1 of thymol; 420 µL L-1 of carvacrol; 210 µL L-1 of thymol and 210 µL L-1 of carvacrol. The control treatment consisted of the MS medium without any phytoregulators. The main components of EO from L. gracilis are carvacrol, ρ-cimene, and thymol. Seven days after the initiation of the experiments, 36.3% of the control treatment shoots were necrotized, but 90% of the caulinary shoots exposed to EO, thymol, or carvacrol appeared necrotized. Transmission electron microscopy of the shoots revealed that the treatment with EO, thymol, or carvacrol caused the destruction of the plasma cell membranes, and the cell organelles and the nucleus were hardly evident. The EO and its main constituent were toxic to caulinary shoots of heliconia. O efeito do timol, carvacrol e óleo essencial de Lippia gracilis foi observado sobre ápices caulinares de heliconia. Após a desinfestação os ápices foram inoculados em meio MS com os tratamentos de 420 µL L-1 do óleo essencial (OE) de L. gracilis; 420 µL L-1 de timol; 420 µL L-1 de carvacrol; 210 µg L-1 de timol e 210 µL L-1 de carvacrol. O tratamento controle consistiu de meio MS sem fitorreguladores. Os principais componentes do OE foram carvacrol, ρ-cimeno e timol. Sete dias após o início do experimento 36,3% dos ápices submetidos ao tratamento controle e 90% dos ápices caulinares expostos ao EO, timol ou carvacrol necrosaram. A microscopia eletrônica de transmissão dos ápices caulinares revelou que os tratamentos com OE, timol e carvacrol provocaram desestruturação da membrana plasmática das células. As organelas e o núcleo não estavam evidentes. O OE e seus principais constituintes foram tóxico para os ápices caulinares de helicônias.